Integration of Theism into Hobbes’s State of Nature (Philosophy and Progress, 2022)
Political philosophers often draw their conclusions on how political systems ought to be by first investigating human nature and then proposing recommendations extrapolating from those investigations. They attempt to do this by creating a hypothetical ‘state of nature’ where human beings would be unaffected by social, political, and cultural paradigms and can act freely in pursuit of their instincts, thereby revealing their true nature. English philosopher Thomas Hobbes followed this method of investigation and found that human beings are naturally violent, individualistic, and warlike and therefore concluded that political theory ought to be as such to prevent human beings from acting out their baser impulses through draconian authoritative measures when necessary. In this paper, I challenge Hobbes’s claim on human nature by citing contemporary research on cognitive sciences which demonstrates that human beings have a natural predisposition to believe in supernatural agency (God/s) and therefore in the state of nature must behave in such a way as contemporary psychologists discovered investigating the effect of religiosity on human beings such as increased cooperation, selfless behavior towards genetically unrelated strangers, reduced crime rate deterred by supernatural punishment, etcetera. I argue that if we take into account the human propensity to believe in the supernatural agency then the state of nature hypnotized by Hobbes would need to be modified and therefore so would his political theory. Given the integration of cognitive science of religion into the state of nature, I conclude that the ideal political system must be centered around religion.Philosophy and Progress, Vol#67-68; No#1-2; Jan-Dec 2020 P 77-118